2019
DOI: 10.1021/jacs.8b10659
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking Active Biopolymer Networks with a Synthetic Hydrogel

Abstract: Stiffening due to internal stress generation is of paramount importance in living systems and is the foundation for many biomechanical processes. For example, cells stiffen their surrounding matrix by pulling on collagen and fibrin fibers. At the subcellular level, molecular motors prompt fluidization and actively stiffen the cytoskeleton by sliding polar actin filaments in opposite directions. Here, we demonstrate that chemical cross-linking of a fibrous matrix of synthetic semiflexible polymers with thermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 54 publications
0
24
1
Order By: Relevance
“…The 2D shape of TiNSs, which eliminates the possibility of entanglement, may be the reason for the excellent rapidity and reversibility of the thermal response of TiNS-Gel. These properties appear to be superior to those of conventional hydrogels based on 1D materials such as organic polymers or nanofibers [1][2][3][4][5][6][7][8][9][10][11][12][13] . Although poly(N-isopropylacrylamide) and related organic polymers have long been the components of choice for smart soft materials 42,43 , we have demonstrated that TiNS can serve as an alternative to such organic polymers.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The 2D shape of TiNSs, which eliminates the possibility of entanglement, may be the reason for the excellent rapidity and reversibility of the thermal response of TiNS-Gel. These properties appear to be superior to those of conventional hydrogels based on 1D materials such as organic polymers or nanofibers [1][2][3][4][5][6][7][8][9][10][11][12][13] . Although poly(N-isopropylacrylamide) and related organic polymers have long been the components of choice for smart soft materials 42,43 , we have demonstrated that TiNS can serve as an alternative to such organic polymers.…”
Section: Discussionmentioning
confidence: 93%
“…This seems considerably difficult because living organisms usually consist of water-rich flexible solids with a structural hierarchy that are capable of responding to stimuli, unlike inorganic materials, which generally exhibit poor processability, low flexibility, and a lack of responsiveness. Indeed, previous studies on biomimetic soft materials have almost exclusively involved the use of organic constituents [1][2][3][4][5][6][7][8] , as typically represented by mechanically adaptive hydrogels based on thermoresponsive organic polymers such as poly(N-isopropylacrylamide) [7][8][9][10][11][12][13] . However, if counterparts of these hydrogels consisting entirely of inorganic materials were to become available, they could expand the scope of materials science by adopting a complementary role to organic-based biomimetic soft materials in providing such characteristics as good mechanical properties, long-term durability, and low environmental burdens [14][15][16] .…”
mentioning
confidence: 99%
“…16,17 Yet, up to today and to the best of our knowledge, the analysis techniques employed for the study of mechanical failure in materials are limited to the macro-scale. However, a holistic description of fracture mechanisms requires to precisely resolve smaller feature-sizes on the micro-scale, as this information is valuable for tailor-making polymeric structures with distinct mechanical properties, such as biomimetic gels, 18 smart skin, 19 or muscle-like materials. 20 Here we report the integration of the Diels-Alder adduct of a π-extended anthracene and maleimide, previously synthesized in our group, 21 as covalent crosslinker into PNIPAAm hydrogel networks, endowing these soft materials with stresssensing capability (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…In another well‐known bis‐urea supramolecular system based on bis(ureido)‐toluene derivates studied in great detail by Bouteiller and coworkers, 25,26 variation of the position of the methyl substituent on the aromatic spacer gave rise to different self‐association and solubility in polar solvents 27 . In our group, much research has been aimed at self‐assembly of oligo(ethylene glycol) (OEG) bis‐urea based bolaamphiphiles in aqueous solution 28,29 and the development of strain‐stiffening hydrogels to mimic the unique mechanical properties of the extracellular matrix 11,30 . In general, a bolaamphiphilic bis‐urea monomer combines two polar hydrophilic OEG outer moieties to increase water solubility and a linear hydrophobic alkyl core that promotes aggregation into micelles.…”
Section: Introductionmentioning
confidence: 99%
“…27 In our group, much research has been aimed at self-assembly of oligo(ethylene glycol) (OEG) bis-urea based bolaamphiphiles in aqueous solution 28,29 and the development of strain-stiffening hydrogels to mimic the unique mechanical properties of the extracellular matrix. 11,30 In general, a bolaamphiphilic bis-urea monomer combines two polar hydrophilic OEG outer moieties to increase water solubility and a linear hydrophobic alkyl core that promotes aggregation into micelles. Hydrogen bonding of the urea groups in the hydrophobic core further directs and strengthens aggregation.…”
Section: Introductionmentioning
confidence: 99%